Penerapan Data Mining Untuk Analisa Kualitas Produk Welding Dengan Algoritma Naïve Bayes Dan C4.5 Pada PT. Karya Bahana Unigam - Ismasari Nawangsih; Junisa Sahar (Jurnal SIGMA, 2022)
PT Karya Bahana Unigam is an automotive seat company, based on the results of testing the C.45 and Naïve Bayes algorithms which are used to produce classifications from data testing. The results of research or observations using different data with the same amount of data but having different attributes, labels and classes, the Naïve Bayes algorithm has optimal classification results because the levels of accuracy, precision and recall have an average of above 70% to 90%, because data in general can be categorized as good data because data has a complete number of attributes and classes and has information on each attribute, label and class in the data used so that it can provide information in improving quality at the testing stage of the C.45 algorithm. 96.00%, Precision 95.00% and Recall 79.17% while the Naïve Bayes accuracy algorithm is 99.33%, Precision 96.00% and Recall 100.00%. Keywords: Data Mining, C.45, Naïve Bayes